Partnership Governance Strategy from a Corporate Perspective: A Case Study of PT. PSD in Strengthening the KDMP - Karismatul Mufidah; Nafidatun Nikmah; Akhmad Sirojudin Munir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines corporate partnership management strategies to address rural economic development gaps, using a case study of PT. Perekonomian Sunan Drajat (PT. PSD) in strengthening the Merah Putih Village Cooperative (KDMP). This partnership was established in response to the weak institutional capacity of village cooperatives, which hinders economic equality. The novelty of this research lies in its focus on corporations as central actors, unlike previous studies that have emphasized the role of the government. Using an exploratory case study qualitative method, this study aims to understand the construction and implementation of PT. PSD's partnership strategy. The main results show that the strategy applied is a hybrid model that synergizes three theoretical foundations: normative motivation (normative isomorphism), resource-based execution (Resource-Based View), and measurable business evaluation (cross-sector social partnership). This model is operationalized through intensive assistance integrated with the company's strategic divisions and participatory decision-making mechanisms. The research conclusion presents the initial concept of “Strategic Corporate-Cooperative Partnership” as a replicable governance framework and recommends the need for government policies that support value-based partnerships and intensive assistance to accelerate the institutional transformation of village cooperatives.